2017
DOI: 10.1038/onc.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

VEGFA links self-renewal and metastasis by inducing Sox2 to repress miR-452, driving Slug

Abstract: Cancer stem cells (CSC) appear to have increased metastatic potential, but mechanisms underlying this are poorly defined. Here we show that VEGFA induction of Sox2 promotes EMT and tumor metastasis. In breast lines and primary cancer culture, VEGFA rapidly upregulates SOX2 expression, leading to SNAI2 induction, EMT, increased invasion and metastasis. We show Sox2 downregulates miR-452, which acts as a novel metastasis suppressor to directly target the SNAI2 3′-untranslated region (3′-UTR). VEGFA stimulates So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 99 publications
5
59
0
Order By: Relevance
“… 22 , 23 In addition, VEGFA has been found to contribute to tumor growth and metastasis by inducing angiogenesis via the VEGFR-1 and VEGFR-2. 21 , 22 , 24 In TC, VEGFA expression was increased in the TC tissues, and overexpression of VEGFA was correlated with the pathologic parameters and metastatic status of the thyroid carcinomas. 25 , 26 In this study, we identified VEGFA as a target of miR-622 in TC.…”
Section: Discussionmentioning
confidence: 96%
“… 22 , 23 In addition, VEGFA has been found to contribute to tumor growth and metastasis by inducing angiogenesis via the VEGFR-1 and VEGFR-2. 21 , 22 , 24 In TC, VEGFA expression was increased in the TC tissues, and overexpression of VEGFA was correlated with the pathologic parameters and metastatic status of the thyroid carcinomas. 25 , 26 In this study, we identified VEGFA as a target of miR-622 in TC.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the high level of ZEB1, another EMT-related transcription factor, was strongly associated with the presence of VM in 96 prostate cancer samples (P < 0.05) 37. In breast cancer, VEGFA led to EMT by up-regulating SOX2 expression in vivo and in vitro 39. VEGFA could stimulate EMT of pancreatic neuroendocrine tumour cells in vitro 38.…”
mentioning
confidence: 91%
“…VEGFA could stimulate EMT of pancreatic neuroendocrine tumour cells in vitro 38. In breast cancer, VEGFA led to EMT by up-regulating SOX2 expression in vivo and in vitro 39. VEGFA could sustain EMT in sonic hedgehog medulloblastoma stem cells via Nrp2 40.…”
mentioning
confidence: 95%
“…VEGFA mainly functions by binding to the receptors, especially VEGFR2, and activates the VEGFR2-dependent signaling pathways 41 . Moreover, VEGFA can accelerate tumor progression by promoting EMT and metastasis 42 . In patients with colorectal cancer liver metastasis, VEGFA could be a prognostic biomarker 43 .…”
Section: Discussionmentioning
confidence: 99%